The Role of Exosomal Non-Coding RNAs in Coronary Artery Disease - Liu, Jia; Wu, Junduo; Li, Longbo; Li, Tianyi; Wang, Junnan (Frontiers in Pharmacology, 2020)
Cardiovascular disease (CVD) remains the leading cause of morbidity and mortality worldwide. Atherosclerosis(AD) is a major cause of CVD. Oxidative stress, endothelial dysfunction and inflammation are key factors in the development and progression of AD. Exosomes are nano-sized vesicles secreted into the extracellular space by most types of cells, which are considered to be ideal substances for the transmission and integration of signals between cells. Cells can selectively encapsulate biologically active substances, such as lipids, proteins and RNA in exosomes and act through paracrine mechanisms. Non-coding RNAs (ncRNAs) are important for communication between cells. They can reach the recipient cells through exosomes, causing phenotypic changes, playing a molecular regulatory role in cell function. Understanding its molecular mechanisms can help identify therapeutic targets or strategies for CVD. This paper reviews the role and the regulatory mechanism of exosomal ncRNAs in the pathophysiological process of coronary artery disease(CAD), as well as the potential contribution of exosomal ncRNA to diagnosis and treatment of CAD.